Design and Application of Railway Locomotive Maintenance Data Integration and Sharing Platform - ZHAO Chao; YANG Yongtao; LAN Fan (Kongzhi Yu Xinxi Jishu)
In order to solve the problems of difficult data integration, complex governance and low sharing efficiency, this paper proposes a scheme for construction of railway locomotive maintenance data integration and sharing platform. The author first realized the automatic and periodic data acquisition from different systems and saving of the same in a data warehouse through multi-source heterogeneous data acquisition technology, and then classified the data in the data warehouse for standardized management and forming service themes and thematic libraries. At the same time, the author also provided real-time and offline data sharing modes under security control, realizing data sharing in different scenarios. This platform, after being constructed in the field, saves more than 70% of the planned time for locomotive pre-scheduling and maintenance, and reduces the average downtime of locomotive maintenance by about 20 minutes. This shows the platform can help to promote multi-system data fusion and improve the informatization level, production efficiency and management ability of railway locomotive maintenance.